Megalencephalic Leukoencephalopathy: Insights Into Pathophysiology and Perspectives for Therapy - Bosch, Assumpció; Estévez, Raúl (Frontiers in Cellular Neuroscience, 2021)
Megalencephalic leukoencephalopathy with subcortical cysts (MLC) is a rare genetic disorder belonging to the group of vacuolating leukodystrophies. It is characterized by megalencephaly, loss of motor functions, epilepsy and mild mental decline. In brain biopsies of MLC patients, vacuoles were observed in myelin and in astrocytes surrounding blood vessels. It is mainly caused by recessive mutations in MLC1 and HEPACAM (also called GLIALCAM) genes. These variants are called MLC1 and MLC2A with both types of patients sharing the same clinical phenotype. In addition, dominant mutations in HEPACAM have also been identified in a subtype of MLC patients (MLC2B) with a remitting phenotype. MLC1 and GlialCAM proteins form a complex mainly expressed in brain astrocytes at the gliovascular interface and Bergmann glia at the cerebellum. It has been previously shown that these proteins regulate several ion channels and transporters involved in the control of ion and water fluxes in glial cells, either directly influencing their location and function, or indirectly regulating associated signal transduction pathways. However, the MLC1/GLIALCAM complex functions and the related pathological mechanisms leading to MLC are still unknown. It has been hypothesized that, in MLC, the role of glial cells in brain ion homeostasis is altered in both physiological and inflammatory conditions. There is no therapy for MLC patients, only supportive treatment. As MLC2B patients show a MLC reversible phenotype, we speculated that the phenotype of MLC1 and MLC2A patients could also be mitigated by re-introduction of the correct gene even at later stages. To prove this hypothesis, we injected in the cerebellar subarachnoid space of Mlc1 knockout mice an adeno-associated virus coding for human MLC1 under the control of the glial-fibrillary acidic protein promoter. MLC1 expression in the cerebellum extremely reduced myelin vacuolation at all ages in a dose-dependent manner. This preclinical study could be considered as the first therapeutic approach for patients affected by MLC. We also suggest in this review other potential therapeutic strategies.